1987
DOI: 10.1159/000242669
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Plasma Arachidonic Acid Binding Capacity in Neonates

Abstract: Arachidonic acid (AA) metabolites have been implicated in neonatal pathologic states such as respiratory distress syndrome (RDS). Since free (nonprotein bound) AA is the substrate for synthesis of these compounds, a decreased capacity to bind AA in neonatal plasma could contribute to these disorders. AA binding was assayed by equilibrium dialysis in plasma samples from healthy adults and various infant groups. Plasma from these infant groups bound significantly less AA than adult plasma. Premature infants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It is possible that some component of neonatal serum further reduces the concentration of arachidonic acid available to the enzyme. However, it is unlikely that this arachidonic acid sink is plasma albumin or another plasma protein because we have previously shown that plasma from neonates has less "binding capacity" for arachidonic acid than that found in adult plasma (23).…”
Section: Resultsmentioning
confidence: 95%
“…It is possible that some component of neonatal serum further reduces the concentration of arachidonic acid available to the enzyme. However, it is unlikely that this arachidonic acid sink is plasma albumin or another plasma protein because we have previously shown that plasma from neonates has less "binding capacity" for arachidonic acid than that found in adult plasma (23).…”
Section: Resultsmentioning
confidence: 95%